POTENTIAL OF MIRNA-183, MIRNA-29B, AND MIRNA-34A COMBINATION AS A NOVEL ADVANCED SENSORINEURAL HEARING LOSS DIAGNOSTIC AND THERAPEUTIC (THERAGNOSTIC) AGENT - Agyta Hanifa Faiza; Gabriela Valencia Putri Husodho; Anatalya Diah Ayu Kumalasari (Jurnal Kedokteran Diponegoro (Diponegoro Medical Journal), 2025)
Background: Sensorineural hearing loss (SNHL) is a hearing disability that makes up 90% of all hearing loss in general. This condition reduces quality of life and causes lifelong disability. Current diagnostic and therapeutic agents are considered less than optimal and need to be developed further. MicroRNAs (miRNAs), such as miRNA-34a, miRNA-29b, and miRNA-183, play a role in the pathogenesis of SNHL and thus have potential as specific biomarkers and therapeutic agents. Objective: To open a new perspective regarding the use of diagnostic biomarkers and miRNA therapy as a new step towards the era of personalized medicine in SNHL patients. Methods: This literature review used a non-systematic review method using the search engines PubMed, Science Direct, and ProQuest. Results: Increased expression of miRNA-34a, miRNA-29b, and miRNA-183 causes a decrease in the number of inner hair cells hence causing hearing loss. This means that these miRNAs can be used as biomarkers in the diagnosis of SNHL. Suppression of these miRNAs to certain levels could potentially be a therapy for SNHL, as it showed reduced oxidative stress and apoptosis. Suppression of miRNA-29b expression causes increased proliferation and reduced oxidative stress. However, knock out of miRNA-183 shows disruption in stereociliary bundle development and hair cell maturation hence when using miRNA inhibitors as therapy it is important to take note of dosage. Conclusion: miRNA-34a, miRNA-29b, and miRNA-183 have potential as diagnostic biomarkers and therapeutic agents for SNHL by regulating levels of oxidative stress, apoptosis, and the number of inner hair cells. Utilizing these three miRNAs simultaneously can increase the specificity, sensitivity and effectiveness in the diagnosis and therapy of SNHL.